Implementation of the Magrib Mengaji Program in Increasing Children’s Motivation to Learn the Qur’an in Mekar Sawit Village - Putri, Anggun Syariani (Yayasan Rahmat Islamiyah, 2026)
The Magrib Mengaji program is a religious education initiative designed to enhance children’s motivation and ability to learn the Qur’an. This study aims to describe the implementation of the Magrib Mengaji Program in Mekar Sawit Village and analyze its effectiveness in increasing children’s Qur’anic learning motivation. This research employed a descriptive qualitative approach using observation, interviews, and documentation as data collection techniques. The findings indicate that the program is well implemented through various learning methods, including tahsin, talaqqi, educational games, and a reward system. Children’s enthusiasm is demonstrated through increased attendance, active participation, and their willingness to review memorization at home. Additionally, parental support and the strong religious environment play a crucial role in enhancing children’s motivation to learn the Qur’an. Therefore, the Magrib Mengaji Program is proven to be an effective medium for religious development and for improving children’s motivation to study the Qur’an.